Individual changes in preclinical spinocerebellar ataxia identified via increased motor complexity. Issue 12 (26th October 2016) - Ilg, Winfried; Fleszar, Zofia; Schatton, Cornelia; Hengel, Holger; Harmuth, Florian; Bauer, Peter; Timmann, Dagmar; Giese, Martin; Schöls, Ludger; Synofzik, Matthis
ABSTRACT: Background: Movement changes in autosomal‐dominant spinocerebellar ataxias are suggested to occur many years before clinical manifestation. Detecting and quantifying these changes in the preclinical phase offers a window for future treatment interventions and allows the clinician to decipher the earliest dysfunctions starting the evolution of spinocerebellar ataxia. We hypothesized that quantitative movement analysis of complex stance and gait tasks allows to (i) reveal movement changes already at early stages of the preclinical phase when clinical ataxia signs are still absent and to (ii) quantify motor progression in this phase. Methods: A total of 46 participants (14 preclinical spinocerebellar ataxia mutation carriers [spinocerebellar ataxias 1, 2, 3, 6], 9 spinocerebellar ataxia patients at an early stage; 23 healthy controls) were assessed by quantitative movement analyses of increasingly complex stance and walking tasks in a cross‐sectional design. Results: Body sway in stance and spatiotemporal variability in tandem walking differentiated between preclinical mutation carriers and healthy controls ( P < .01). Complex movement conditions allowed one to discriminate even those mutation carriers without any clinical signs in posture and gait (SARAposture&gait = 0; P < .04). Multivariate regression analysis categorized preclinical mutation carriers on a single‐subject level with 100% accuracy within a range of 10 years to the estimated onset. Movement features in stance and gait correlated significantly with genetically estimated time to onset, indicating a gradual increase of motor changes with increasing proximity to disease manifestation. Conclusion: Our results provide evidence for subclinical motor changes in spinocerebellar ataxia, which allow to discriminate patients without clinical signs even on a single‐subject basis and may help capture disease progression in the preclinical phase. © 2016 International Parkinson and Movement Disorder Society